Individual Responses to Heat Stress: Implications for Hyperthermia and Physical Work Capacity - Foster, Josh; Hodder, Simon G.; Lloyd, Alex B.; Havenith, George (Frontiers in Physiology, 2020)
Background Extreme heat events are increasing in frequency, severity, and duration. It is well known that heat stress can have a negative impact on occupational health and productivity, particularly during physical work. However, there are no up-to-date reviews on how vulnerability to heat changes as a function of individual characteristics in relation to the risk of hyperthermia and work capacity loss. The objective of this narrative review is to examine the role of individual characteristics on the human heat stress response, specifically in relation to hyperthermia risk and productivity loss in hot workplaces. Finally, we aim to generate practical guidance for industrial hygienists considering our findings. Factors included in the analysis were body mass, body surface area to mass ratio, body fat, aerobic fitness and training, heat adaptation, ageing, sex, and diabetes (type 1 and type 2). Findings We found the relevance of any factor to be dynamic, based on the work-type (fixed pace or relative to fitness level), work intensity (low, moderate, or heavy work), climate type (humidity, clothing vapour resistance), and variable of interest (risk of hyperthermia or likelihood of productivity loss). Heat adaptation, high aerobic fitness, and having a large body mass are the most protective factors during heat exposure. Primary detrimental factors include low fitness, low body mass, and lack of heat adaptation. Ageing beyond 50 years, being female, and diabetes are less impactful negative factors, since their independent effect is quite small in well-matched participants. Skin surface area to mass ratio and body composition are not strong predictors of the heat stress response. Conclusions: Understanding how individual factors impact responses to heat stress is necessary for the prediction of heat wave impacts on occupational health and work capacity. The recommendations provided in this report could be utilised to help curtail hyperthermia risk and productivity losses induced by heat.